2021
DOI: 10.3947/ic.2020.0100
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Human Immunodeficiency Virus-1 Antiretroviral Drugs: General Principles and Current Status

Abstract: Treatment with highly active antiretroviral therapy (HAART) can prolong a patient's life-span by disrupting pivotal steps in the replication cycle of the human immunodeficiency virus-1 (HIV-1). However, drug resistance is emerging as a major problem worldwide due to the prolonged period of treatment undergone by HIV-1 patients. Since the approval of zidovudine in 1987, over thirty antiretroviral drugs have been categorized into the following six distinct classes based on their biological function and resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…Once HIV-1 enters the target cell, the RNA genome is released, and reverse transcription occurs, ultimately generating DNA [ 71 ]. The viral DNA moves into the nucleus and is integrated into the host genome by viral integrase [ 71 ]. Once fully integrated, HIV-1 is considered a provirus.…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%
See 1 more Smart Citation
“…Once HIV-1 enters the target cell, the RNA genome is released, and reverse transcription occurs, ultimately generating DNA [ 71 ]. The viral DNA moves into the nucleus and is integrated into the host genome by viral integrase [ 71 ]. Once fully integrated, HIV-1 is considered a provirus.…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%
“…Viral mRNA is used for the transcription of other viral proteins (e.g., gp120, gp41, negative regulatory factor (Nef), viral protein U (Vpu), and group-specific antigen (Gag)). If the full length of the viral mRNA is expressed, it is eventually packaged into a progeny virus as the viral genome [ 71 ].…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%
“…In the drug class of NRTIs, the US Food and Drug Administration (FDA) approved zidovudine (AZT) in March 1987, followed by didanosine (ddI) in October 1991, zalcitabine (ddC) in June 1992, stavudine (d4T) in June 1994, lamivudine (3TC) in November 1995, abacavir (ABC) in December 1998, tenofovir disoproxil fumarate (TDF) in October 2001, and emtricitabine (FTC) in July 2003. In the drug class of NNRTIs, nevirapine (NVP), delavirdine (DLV), efavirenz (EFV), and etravirine (ETR) were approved by the FDA 4 , 12 , 13 , 14 . The “old” generation of the preceding RT inhibitors is often challenged by the emergence of drug resistance and adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the development and approval of new drugs require substantial investment and time, drug repurposing has gained considerable attention in recent years ( 94 ). For instance, Artesunate has been approved by the FDA for the treatment of severe malaria ( 95 ); rapamycin is an FDA-approved immunosuppressant administered to organ transplantation patients ( 96 ); and Zalcitabine is a nucleoside reverse-transcriptase inhibitor approved by the FDA for HIV treatment ( 97 ). Recent studies have demonstrated their potential to induce ferroptosis and exhibit antitumor effects.…”
Section: Discussionmentioning
confidence: 99%